Antigenotoxic properties of anthocyanin-enriched fraction of strawberry (cv. Romina) extract on DNA damage induced by H2O2 in human peripheral blood leukocytes - Spremo-Potparević, Biljana; Čabarkapa-Pirković, Andrea; Dekanski, Dragana; Topalović, Dijana; Bajić, Vladan; Živković, Lada (Archives of Pharmacy, 2021)
Strawberry fruit Fragaria × ananassa Duchesne, Rosaceae (cv. Romina), rich in anthocyanin polyphenols, has been demonstrated to have favorable effects on health due to its antioxidant properties. The present study investigated the antigenotoxic potential of anthocyanin-enriched fraction of Romina strawberry methanolic extract (ACY) against DNA damage on human peripheral blood leukocytes, induced by hydrogen peroxide in vitro. Five concentrations of the ACY extract were used in all experiments (2.5, 5, 10, 15, 20 µg/ml). The results of the alkaline comet assay showed no genotoxic effect of the ACY. After the pre-exposure of the leukocytes to the ACY, and subsequent incubation with H2O2, a decreased number of DNA damaged cells was recorded in all the tested concentrations, compared to controls. In the post-treatment, there was a concentration-dependent DNA damage reduction, while a statistically significant decrease was achieved with 15 and 20 µg/ml concentrations. The results indicate that ACY is efficient in oxidative DNA damage reduction, and it is more potent as a post-applicative than a protective agent.